Chronic care, health care systems, and services integration - Kronenfeld, Jennie J. (Research in the sociology of health care ;, 2004)
The theme of this volume is chronic care, health care systems and services integration. The volume is divided into three sections. The first section focuses on issues that relate to health care providers. The second section contains papers that deal with home and community based services for the elderly and those who need chronic care. The third section provides lessons from countries outside the United States related to the overall themes of chronic care, systems integration and services integration. These are themes of growing importance in the US health care system as well as in health care systems in most other developed nations. The aging of populations, already underway, and expected to increase in the coming decades will bring changes and challenges to the health care system. Many of these challenges relate to chronic care needs, since chronic care needs are more important in the elderly than in other population groups, although chronic care problems are not limited to the elderly. Once people reach their 40s and 50s, they begin to develop chronic problems. Chronic problems often require both more health care services and more complicated health care services, and thus place an emphasis on services integration.